CHECKING THE STUDENT’S APTITUDE FOR A BACHELOR PROGRAM: EXPERIENCES WITH A WEB-BASED TOOL - Jüngling, Stephan; Telesko, Rainer; Reber, Andreas (PUPIL: International Journal of Teaching, Education and Learning, 2018)
In autumn 2014 the Bachelor of Science programme “Business Information Technology (BSc BIT)” was launched. BIT is about the application of information technology in business with the focus on building information systems. Since the start of the programme it can be observed that a considerable number of students face difficulties in modules related to programming and mathematics at the beginning of the study. In order to help potential applicants of the programme to understand the kind of competencies of abstract thinking that are needed for the BSc BIT programme ahead of the start, a web based self-assessment test was developed. The aptitude test - built with Google Forms - currently consists of 25 predefined multiple choice questions and calculates an overall aptitude figure by summing up the single aptitude values for the categories logical and analytical thinking, understanding algorithms, mathematics and abstract thinking. The questions are taken from well-established test systems like ELIGO-System, BOMAT, CASA etc. and are typically solved within less than 45 minutes. The students can check their suitability for the study programme by comparing their overall aptitude value with a given threshold. First test runs conducted with the tool confirm the validity of the aptitude test. The future scope will involve more students and deal with an analysis of concrete weaknesses that can be used as input to adapt the settings of programming and mathematics modules.